SCHEDULING STUDY ON THE FACULTY OF MEDICINE COLLEGE BUILDING PROJECT INDONESIAN MUSLIM UNIVERSITY - Wudi Darul Putra (Magister Teknik Sipil Pps Universitas Muslim Indonesia, 2021)
A construction project is an activity that has a certain period of time, with limited resources to carry out a predetermined task in the form of building/repairing facilities (buildings, roads, bridges, dams). This study aims to [1] Optimal scheduling planning in order to obtain maximum profit by using the